Algısal Homofili ve Marka-Fenomen Uyumu Perspektifinden Sosyal Medya Fenomenlerinin Marka Tutumuna Etkisi - Baruönü, Özge (Muş Alparslan Üniversitesi, 2021)
Infleuncer marketing, a new form of social media advertising, has been frequently by brands in recent years.In this study, a conceptual model that demonstrates the effective factors in creating a positive consumer attitude and purchasing intention regarding the brands supported by social media influencers is proposed and tested with an empirical study. In May 2020, an online survey was conducted with 124 participants following at least one social media influencer.The findings reveal the positive impact of influencer in affecting consumer attitudes and purchasing intentions. It specifically underlines that marketing managers should consider the attractiveness and reliability of influencer beside influencer-brand compatibility, and influencer-target population similarity when choosing the influencer to support their brand.

Çalışmada, sosyal medya fenomenlerinin destekledikleri markalarla ilgili olarak pozitif tüketici tutumu ve satın alma niyeti oluşturmalarında etkili faktörleri ortaya koyan kavramsal bir model önerilmiş ve ampirik bir çalışma ile test edilmiştir. En az bir sosyal medya fenomenini takip eden 124 katılımcıyla çevrimiçi anket yoluyla gerçekleştirilen tanımlayıcı araştırmanın bulguları, tüketici tutumlarını ve satın alma niyetlerini etkilemede sosyal medya fenomenlerinin etkisini ortaya koymakta, ayrıca markalarını desteklemek için sosyal medya fenomenlerini belirlerken, pazarlama yöneticilerinin fenomen çekiciliğini, güvenilirliğini ve fenomen-marka uyumunu ve fenomen hedef kitle benzerliğini de (algısal homofili) dikkate almaları gerektiğinin altını çizmektedir.
Effects of Social Media Influencers on Brand Attitude From the Perspective of Brand-Influencer Compatibility and Perceived Homophily
anemon
Keywords: Influencer; Social media; Perceived homophily; Brand; Brand-Influencer Compatibility; Fenomen; Sosyal medya; algısal homofili; marka; Marka-Fenomen Uyumu